Hubungan Pengetahuan dan Tingkat Konsumsi Zat Besi, Asam Folat, Vitamin C, Protein dan Energi Dengan Kejadian Anemia Ibu Hamil di Puskesmas Seririt 1 Kabupaten Buleleng - Cahyani, Kadek Rahayu; Mataram, M.Kes, Dr. Ir. I Komang Agusjaya; SKM, M.Kes, Ida Ayu Eka Padmiari (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2025)
Anemia is a condition of insufficient or low concentrations of hemoglobin (Hb), erythrocytes and hematocrit (Hct) from normal values. Pregnant women experience anemia if their hemoglobin (Hb) level is below 11 g/dL. The aim of this research is to determine the relationship between knowledge and levels of consumption of Iron, Folic Acid, Vitamin C, Protein and Energy with the incidence of anemia in pregnant women. This type of research is observational with a cross sectional design. Carried out in December 2023. The sample size was 50 samples determined from 98 pregnant women in the Seririt I Community Health Center Working Area, Buleleng Regency. Sampling was carried out using purposive sampling. Data analysis used the Pearson Correlation test. Based on the results of sample observations, it was found that 54.0% were Anemic, 42.0% had poor knowledge, 54.0% had a poor level of Iron consumption, good Folic Acid, 52.0% had a good level of Vitamin C consumption, 52.0% had a good level of Protein consumption 56.0% and the energy consumption level is 54% less. The results of statistical tests showed that there was no relationship between levels of iron consumption (p= 0.296 ; r= 0.151), folic acid (p= 0.184 ; r= 0.191), vitamin C (p= 0.488 ; r= 0.101), protein (p= 0.849 ; r= 0.028), energy p= 0.527 ; r= 0.092) with knowledge of pregnant women. There is a relationship between the level of iron consumption (p= 0.001 ; r= 0.744), Folic Acid (p= 0.001 ; r= 0.660), Vitamin C (p= 0.001 ; r= 0.697), Protein (p= 0.001 ; r=0.491), Energy (p= 0.001 ; r=0.678) with anemia status in the Seririt 1 Community Health Center Working Area, Buleleng Regency.Keywords: knowledge, iron consumption level, folic acid, vitamin C, protein, energy anemia of pregnant woman